DESIGN OF A MOBILE CRANE TO LIFT DAMAGED VEHICLES WITH A CAPACITY OF 6 TONS - Harapan Budianto; Samuel Haris Purba (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
This study discusses the design of a mobile crane to lift damaged vehicles with a capacity of 6 tons with the aim of analyzing the planning of the lifting system used ; planning the rope to be used ; transmission system ; calculation of the components of the lifting equipment used ; calculation of power to rotate the drum ; the tool designed is a mobile crane with a capacity of 6 tons to 6 tons ; and calculating the lifting time. assembly . Type of drive motor with Combustion engine = internal combustion engine , Drive motor power = 192.36 Hp , Drive motor rotation = 2740 rpm , Max lifting capacity = ton , Lifting height = 3 m . Drum with Drum diameter = 300 mm , Drum pitch = 16 mm , Drum length = 300 mm , Maximum compressive stress of material = 1600 kg/cm 2 The maximum compressive stress that occurs = 1173.6 kg/cm 2 . Steel rope ( Rope type = 6 x 9 x 1 fc , Rope cross-sectional area = 1173.6 kg/cm 2 . = 2.9 cm 2 , Wire diameter = 1.18 mm , Diameter of steel rope = 26.3 mm , Actual fracture stress = 180/199 kg/mm 2 , Fracture loading = 39100 kg/mm 2 , U nut rope usage = 88.2 months ); Pulley ( Type of pulley = fixed pulley , pulley diameter = 4.8 cm , Width of the pulley = 2.2 cm ); Hook ( Hook type = single hook with thread , Thread type on hook = M 42. Length of threaded hook = 42 mm , Number of threads on the hook = 9 threads , Distance between threads = 4.5 mm , Outer diameter on thread = 42 mm , Effective diameter on the thread = 39 mm , Core diameter on thread = 37.129 mm , Hook material = wrought carbon steel SF 60 , Permissible contact stress = 3 kg/mm 2 , The contact stress that occurs = 2.7 kg/mm 2 ); Boom ( Boom type = boom with fixed arm , Number of booms = 2 pieces , Boom length = 4 m , Boom weight = 1568.66 kg , Boom material = steel pipe , Tensile strength of the material = 40 kg/mm 2 , Tensile strength that occurs on the boom = 10 kg/mm 2 ); Gears ( Types of gears = worm gear , type of gear on the shaft material = cross gear , Type of chain used = hinge chain , chain weight per meter = 16.5 kg )